Christian values education and holistic child development in Santiago City, Philippines - Li, Jia (Southeast Asia Early Childhood Journal, 2021)
The study focused on Christian values education and holistic child development in a catholic school and a non-sectarian school both located in Isabela Province. Ten Christian values espoused in a Christian Values Education program was evaluated to be practiced and manifested and correlated to five holistic child development domains. A total of 100 parent respondents come from each of the Catholic and Non-Sectarian school through random sampling. It employed a survey assessment tool gathered results were treatment statistically aligned with study objectives. The study reveals that based on computed r-values, there is a significant correlation between Christian value education and holistic child development at .01 level of significance among pupils of a Catholic School while in non-sectarian school, computed r-values indicate that there is no significant correlation between Christian value education and holistic child development at p-value .01 level of significance except in emotional and spiritual development among pupils of a non-sectarian school. Moreover t-value results reveal that there are significant differences in Christian Values repentance, reconciliation, faith, worship of God, perseverance, obedience and hope while there is not significant different in the Christian values of stewardship, trustworthiness and responsibility among pupils in a Catholic and Non Sectarian School. While for holistic child development, t-value results reveal that there are significant differences in all holistic child development aspects among pupils of a Catholic and Non-Sectarian School except in the aspect of physical development where there is no significant difference found in this development area.